Psychological Capital and Social Capital as influencers of Innovative Work Behaviour (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The ability to improve its products, services, work  procedures and to innovate continuously has  become crucial for any organization. The higher  education sector is always fueled by ever-growing  demand for capabilities and competencies and for  institutions to thrive in this highly competition  driven era, they must respond in novel ways to  meet this demand. Amidst stiff competition, swift  advances in new technologies and changing needs  of the international labor markets, the sector  itself presents a fertile ground for pioneering  innovations. Therefore, the institutions must  understand how innovations are developed and  how employees’ work behaviour is related to this  process. The present study tries to examine the  relationship between Psychological Capital and  Social Capital as influencers of Innovative Work  Behaviour of the teaching professionals of this  sector in Assam.
Keywords: innovate; competition; innovations